2013
DOI: 10.1016/j.snb.2013.03.136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polytetrafluoroethylene or polyimide coating on H2 sensing properties of anodized TiO2 films equipped with Pd–Pt electrodes

Abstract: Diode-type H 2 sensors based on anodically oxidized TiO 2 thin films equipped with Pd-Pt electrodes (Pd-Pt/T-TiO 2 , T-TiO 2 represents the TiO 2 thin film fabricated by the anodization of the pre-oxidized Ti plate at 600°C for 1 h in air) have been fabricated, and the effects of the polymer coating on the Pd-Pt/T-TiO 2 sensor to humidity and oxygen partial pressure on the sensing properties to 500~8,000 ppm H 2 under dry and wet atmospheres have been investigated in this study. The films tested were polytetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Hydrophobicity of the polymer film is one of important factors in the water-blocking behavior of PMMA thin film. 21,34 The contact angles of 150 nm PMMA on Pt, and Pt itself, for water were 75…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophobicity of the polymer film is one of important factors in the water-blocking behavior of PMMA thin film. 21,34 The contact angles of 150 nm PMMA on Pt, and Pt itself, for water were 75…”
Section: Methodsmentioning
confidence: 99%
“…21 Yamato et al reported the mitigation of humidity effect and improved hydrogen sensing characteristics of anodized TiO 2 Schottky diode using polytetrafluoroethylene or polyimide coating. 34 At 25…”
mentioning
confidence: 99%
“…All of the layers are deposited by vacuum deposition [30]. The similar type of sensor with PTFE protective film was developed in India [31] and in Japan [32], but they are used for electrical detection of changes occurred in the multilayered film in hydrogen presence. The sensors made in Japan use a multilayered structure: in the case of PI-10/PTFE-10/Pd-Pt/T-TiO 2 sensor, the additional coating of PI-10 on the PTFE increased the magnitude of wet air/dry air sensor response at temperatures lower than 200 °C, in comparison with that of Pd-Pt/T-TiO 2 , leading to the enhancement of the interference from humidity on the H 2 response.…”
Section: Pfp Films In Sensorsmentioning
confidence: 99%
“…The same trend of response and recovery times for other nanoporous metal oxide gas sensors has been reported where the recovery time is generally longer than the response time upon exposure to various analyte concentrations. 41,64 As the concentration of the gas analyte increases, a faster response is demonstrated. Conversely, the recovery time increases as the gas analyte concentration increases.…”
Section: Gas Sensing Performancementioning
confidence: 99%